Patient factors associated with unidentified reactivity in solid‐phase and polyethylene glycol antibody detection methods. Issue 5 (14th March 2017) - Miller, Nichole M.; Johnson, Susan T.; Carpenter, Erica; Naczek, Christine A.; Karafin, Matthew S.
Abstract : BACKGROUND: Several publications have reported an increase in nonspecific reactions when automated technologies such as solid phase are used for the detection of red blood cell alloantibodies. However, there is little known about patient‐specific factors associated with these reactions and the clinical importance of these nonspecific reactions. STUDY DESIGN AND METHODS: We performed a 6‐year retrospective review of our blood bank records and all newly reported unidentified (UID) reactivity using a test tube polyethylene glycol (t‐PEG) and solid‐phase method for the detection and identification of alloantibodies was recorded. Patient factors, such as underlying diagnosis, age, sex, ABO, Rh type, ethnicity, and subsequent antibody formation were recorded in each case. RESULTS: We determined that there was a significant increase in new UID reactions recorded in solid phase (20 per 10, 000 tests) when compared to the t‐PEG (1.8 per 10, 000 tests) method for the detection of antibodies (p ≤ 0.0001). Solid‐phase UID reactions were significantly associated with female sex (p = 0.04) and certain diagnoses, such as chronic or autoimmune disease, cancer, pregnancy, surgery, and trauma. Approximately 16% of patients developed a new auto‐ or alloantibody subsequent to their detected UID using solid phase. CONCLUSIONS: When solid phase is used for antibody identification, there is greater sensitivity toward nonspecific reactivity when compared to the t‐PEG method. Patient sex and underlying diagnosis may explain the increased incidence of new UID reactivity in the solid‐phase technology. Finally, UID reactivity should not be overlooked due to a notable percentage of subsequent clinically significant antibodies after UID detection.